IMPROVING STUDENT LEARNING RESULTS IN MATHEMATICAL LESSONS OF OPERATING MATERIALS CALCULATED THROUGH LEARNING STRATEGIES LEARNING START WITH A QUESTION - Junaedi, Euis Isnaeni; Utomo, Eki Aprianti; Ruqoyyah, Siti (IKIP Siliwangi, 2018)
The research is motivated by the low learning outcomes of the fourth grade students of SDN 042 Gambir in the mathematics subject of number counting operation material, with the aim that students' learning outcomes can increase, also to determine the activities of students and teachers as well as student responses in learning in mathematics subjects operating material count numbers. This study uses the learning strategy Start with a question, which is a learning strategy that makes students learn actively by making them ask about the subject matter before an explanation from the teacher. This study uses Classroom Action Research (CAR) method known as Classroom Action Research (CAR) which aims to improve the quality of the learning process in the classroom. The technique of collecting data through observation, questionnaires, tests and documentation. The respondents were 33 fourth grade students of SDN 042 Gambir. The results of this study were: student learning outcomes in learning operations count numbers before action is still low, this is known from the students' reaching KKM 65 only 39.4% of all students. After the implementation of learning strategies. Student learning outcomes increased to 66.7% in cycle I and to 87.9% in cycle II, teacher and student activities increased and students' responses to learning were quite positive.